Genders - Glover, David; Kaplan, Cora (Routledge, 2000)
"Gender" has, in recent years, become one of the busiest terms in literary and cultural theory, as well as being one of the most contested. David Glover and Cora Kaplan chart the main lines of contemporary debate surrounding gender in a guide which:* presents a history of the term, from the sexology of psychoanalysis of the 1960s to its current usage within the interdisciplinary field of gender studies* looks at the major perspectives on gender from second-wave feminist writers and critics* examines new work on masculinity in literary and cultural studies* assesses how the creation of new queer and gendered identities has impacted the study of literature* surveys empirical and theoretical work on readership and spectatorship, looking in detail at modes of fantasy, cultural consumption, reader response and fan cultures.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; amériques; antiféminisme; approches et analyses; cours; culture populaire; discipline; fem1000; littérature; masculinisme; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; états-unis; études culturelles; études littéraires